A method for regulating the hydrophilic-hydrophobic property of carbon aerogels

CN117963882BActive Publication Date: 2026-11-03BEIJING INST OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410014545.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-04
Publication Date
2026-11-03
Estimated Expiration
2044-01-04

AI Technical Summary

Technical Problem

Existing technologies are difficult to efficiently and cost-effectively control the hydrophilicity and hydrophobicity of carbon aerogels, and the preparation process is complex and lacks universality.

Method used

By preparing phenolic resin solutions, performing gelation, drying, and carbonization, and combining changes in precursors, the addition of metal salts, and control of the sealing properties of the gelation aging process, the hydrophilicity and hydrophobicity of carbon aerogels can be regulated.

Benefits of technology

This method enables low-cost, simple, and universally applicable control of the hydrophilicity and hydrophobicity of carbon aerogels, thereby improving their performance in various application fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117963882B_ABST
    Figure CN117963882B_ABST
Patent Text Reader

Abstract

The application discloses a method for regulating the hydrophilicity and hydrophobicity of carbon aerogel, and adopts resorcinol and formaldehyde as precursors to prepare RF aerogel, which has low cost, simple preparation process and can be prepared in large quantities. The hydrophilicity and hydrophobicity of the final carbon aerogel can be changed by immersing the gel in a salt solution at different reaction periods or directly adding metal salt in the reaction stage, and the regulation method is simple and easy to operate. By regulating the hydrophilicity and hydrophobicity of the surface of the carbon aerogel, the performance of the carbon aerogel in various application fields can be best exerted. For example, when the carbon aerogel is used as a carrier in the field of electrocatalysis, the catalyst sample cannot be too hydrophilic to avoid waterlogging, and cannot be too hydrophobic to make the catalyst unable to play a role. By regulating the hydrophilicity and hydrophobicity of the surface of the carbon aerogel, the catalytic performance of the carbon aerogel in the field of electrocatalysis can be better exerted. When the carbon aerogel is used as an oil absorption material, it needs to be hydrophobic, and by using a simple regulation method, the hydrophobic carbon aerogel can be easily obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of nanoporous materials technology, and more specifically to a method for regulating the hydrophilicity and hydrophobicity of carbon aerogels. Background Technology

[0002] Inspired by nature, hydrophilicity and hydrophobicity have always attracted attention, and existing research has demonstrated their enormous application potential in energy, environment, and information. To obtain superhydrophilic or superhydrophobic materials, surface treatment methods such as oxidation, silicide treatment, and coating are often used to modify the chemical properties and morphology of the material surface in order to control its hydrophilicity and hydrophobicity. However, these methods rely on post-processing of the material to obtain different wettability. However, achieving intrinsic wettability in a material and being able to control the final wettability in the initial stage is an extremely challenging topic, and related research is scarce.

[0003] Carbon aerogels possess unique properties, such as continuous porosity, low density, high specific surface area, high thermal and acoustic insulation, high electrical conductivity, and ultra-high temperature thermal stability in non-oxidizing atmospheres. They can be used as adsorbents, chromatographic coating agents, gas diffusion electrodes, capacitor deionizers, molecular sieves, thermal insulation materials for thermal protection systems, electrodes for supercapacitors or rechargeable batteries, and advanced catalyst supports for fuel cells. Furthermore, carbon aerogels exhibit biocompatibility, making them suitable for manufacturing artificial biological tissues, artificial organs and organ components, medical diagnostic agents, and drug carriers for parenteral drug delivery systems. Existing research reports their low density, large surface area, and high electrical conductivity, indicating significant application potential in numerous fields. However, to date, there has been no exploration of achieving different hydrophilicity / hydrophobicity properties on these materials, and methods for controlling hydrophilicity / hydrophobicity are rarely reported. Controlling the hydrophilicity / hydrophobicity of materials remains a research hotspot in many application fields. Hydrophilicity / hydrophobicity affects the interaction between the material surface and its contacting substances, thus influencing application performance. Therefore, the rational control of the hydrophilicity / hydrophobicity of carbon aerogel surfaces has a significant impact on the application of carbon aerogel materials.

[0004] Ying Jun et al. proposed using resorcinol and furfural as raw materials to prepare carbon aerogels through sol-gel, atmospheric pressure drying, and high-temperature carbonization in a vacuum environment. The carbon aerogels prepared by this method can be transformed from superhydrophilic to superhydrophobic materials after fluorination treatment (Ying Jun, Su Xunjia, Hou Genliang, et al. Preparation and wetting properties of carbon aerogels [J]. Ordnance Materials Science and Engineering, 2012, 35(4):3.). Professor Huang Chaobo's team (Advanced Functional Materials, 2023:2214157.) successfully constructed an aerogel with excellent surface hydrophobicity and bottom hydrophilicity by unidirectional freeze casting of a mixture of HPAN (hydrolyzed polyacrylonitrile), PVA (polyvinyl alcohol), and CNTs (multi-walled carbon nanotubes), followed by freeze drying, thermal crosslinking, in-situ polymerization, and surface modification. CN109364877A also disclosed a method for preparing superhydrophobic fiber carbon aerogels, which can obtain superhydrophobic fiber carbon aerogels. Kai Zhang et al. (Advanced Functional Materials, 2022, 32(26): 2113082.) developed a conductive carbon aerogel with cellulose nanowires (CNF), carbon nanotubes (CNT), and reduced graphene oxide (RGO) through a bidirectional freezing and subsequent annealing process. This resulted in an ultra-low density and excellent hydrophilicity, and it exhibits outstanding performance in applications such as supercapacitors and strain sensors.

[0005] The above only describes the preparation of superhydrophilic or superhydrophobic carbon aerogels for specific materials by adding a specific solvent or using a specific method. It is not universal, and the preparation process is complex and costly. Furthermore, no method has been proposed to control the hydrophilicity or hydrophobicity of carbon aerogels. Summary of the Invention

[0006] In view of the above-mentioned shortcomings in the prior art, the purpose of this invention is to provide a method for regulating the hydrophilicity and hydrophobicity of carbon aerogels that is low in cost, high in efficiency, simple to operate, and universally applicable.

[0007] To achieve the above-mentioned objectives, the technical solution adopted by this invention is as follows:

[0008] A method for controlling the hydrophilicity and hydrophobicity of carbon aerogel is provided, characterized by preparing a phenolic resin solution, followed by gelation, aging, drying, and carbonization to obtain carbon aerogel; and controlling the hydrophilicity and hydrophobicity of the carbon aerogel through any of the following operations:

[0009] a. Change the precursor used to prepare the phenolic resin solution;

[0010] b. Add metal salts during the preparation of phenolic resin solutions;

[0011] c. Soak the gel in a salt solution or organic solvent before carbonization and pyrolysis;

[0012] d. Modify the sealing properties of the gelation and aging processes.

[0013] Furthermore, a phenolic resin solution was prepared using resorcinol and aldehyde as precursors.

[0014] Furthermore, the specific method for preparing the phenolic resin solution is as follows: add resorcinol to an aqueous solution and stir until the solution becomes transparent. Then add sodium carbonate as a catalyst and stir for 1 hour. After stirring, add aldehyde and stir for another hour to obtain the phenolic resin solution.

[0015] Furthermore, the specific methods for gelation and aging are as follows: the thoroughly stirred phenolic resin solution is transferred to a small bottle, sealed, and placed in an 80℃ oven for 4-5 days to obtain a gel.

[0016] Furthermore, the specific drying method is as follows: the gel is transferred to a freeze dryer, freeze-dried for 3 days, and then discharged to obtain an organic aerogel.

[0017] Furthermore, the specific method of carbonization is as follows: the organic aerogel is placed in a tube furnace, the protective gas is nitrogen or argon, the tube furnace is heated at a heating rate of 5℃ / min, and when it is heated to the pyrolysis temperature of 700-1000℃, it is held at the temperature for 3 hours, and after cooling, the material is discharged to obtain carbon aerogel.

[0018] The beneficial effects of this invention are as follows:

[0019] By controlling the hydrophilicity and hydrophobicity of the carbon aerogel surface, its performance in various applications can be optimized. For example, when using carbon aerogel as a support in electrocatalysis, the prepared catalyst sample cannot be too hydrophilic to avoid water flooding, nor too hydrophobic to prevent the catalyst from functioning. By controlling the hydrophilicity and hydrophobicity of the carbon aerogel surface, its catalytic performance in electrocatalysis can be better utilized. When using carbon aerogel as an oil-absorbing material, hydrophobicity is required, and hydrophobic carbon aerogels can be easily obtained through simple control methods. It can be seen that this strategy of controlling the hydrophilicity and hydrophobicity of carbon aerogels has significant practical implications. Attached Figure Description

[0020] Figure 1 The contact angle test results of carbon aerogels with different amounts of manganese nitrate (a:b:c:d:e:f of manganese nitrate introduced = 6:5:4:3:2:1);

[0021] Figure 2 The contact angle test results of carbon aerogels with different amounts of ferric nitrate (the amount of ferric nitrate introduced is a:b:c = 3:2:1);

[0022] Figure 3 Contact angle test results of carbon aerogels subjected to gelation and aging processes with the same amount of cobalt nitrate under different sealing conditions (a. worst sealing b. moderate sealing c. best sealing);

[0023] Figure 4 Contact angle test results of carbon aerogels subjected to gelation and aging processes with the same amount of nickel nitrate under different sealing conditions (a. worst sealing b. moderate sealing c. best sealing);

[0024] Figure 5 Contact angle test results for carbon aerogel and carbon aerogel with different added nitrates (a. carbon aerogel b. carbon aerogel with added Ni(NO3)2 c. carbon aerogel with added Co(NO3)2 d. carbon aerogel with added Mn(NO3)2 e. carbon aerogel with added Fe(NO3)3);

[0025] Figure 6 Contact angle test results for carbon aerogels with different precursors (a. resorcinol and formaldehyde b. resorcinol and furfural c. resorcinol and 2-thiophene formaldehyde);

[0026] Figure 7 The contact angle test results are for carbon aerogels soaked in different solutions before pyrolysis (a. not soaked; b. soaked in an alcoholic solution of trifluoroacetic anhydride before pyrolysis; c. soaked in an alcoholic solution of Mn(NO)3 before pyrolysis). Detailed Implementation

[0027] The specific embodiments of the present invention are described below to enable those skilled in the art to understand the present invention. However, it should be understood that the present invention is not limited to the scope of the specific embodiments. For those skilled in the art, various changes are obvious as long as they are within the spirit and scope of the present invention as defined and determined by the appended claims. All inventions utilizing the concept of the present invention are protected.

[0028] Example 1

[0029] 1.11 g of resorcinol and 0.014 g of Na₂CO₃ were dissolved in 10 ml of water in six parallel portions. The solutions were stirred until clear. Different amounts of manganese nitrate were added, and stirring continued for 1 hour. Then, 2 mL (0.01 mol) of formaldehyde was added to each solution, and stirring continued for another hour. The solutions were transferred to sealed vials and placed in an 80°C oven for 3 days for gelation and aging. The resulting gels were then frozen and dried under vacuum at -50°C in a freeze dryer for three days. The dried samples were then heated in a 1000°C N₂ atmosphere for 3 hours at a heating rate of 5°C / min to obtain manganese-containing carbon aerogels. The hydrophilicity and hydrophobicity of the carbon aerogels with different amounts of manganese nitrate were measured using a contact angle meter. It was found that the higher the amount of manganese nitrate added, the larger the contact angle and the stronger the hydrophobicity of the carbon aerogel. Figure 1 ).

[0030] Example 2

[0031] 1.11 g of resorcinol and 0.014 g of Na₂CO₃ were dissolved in 10 ml of water and stirred until the solution was clear. Three parallel portions were prepared, each with different amounts of ferric nitrate added, and the mixture was stirred for 1 hour. Then, 2 mL (0.01 mol) of formaldehyde was added to each portion, and the mixture was stirred for another hour. The solutions were transferred to sealed vials and placed in an 80°C oven for 4 days for gelation and aging. The resulting gels were then frozen and dried under vacuum at -50°C in a freeze dryer for three days. The dried samples were then heated in a 1000°C N₂ atmosphere for 3 hours at a heating rate of 5°C / min to obtain iron-containing carbon aerogels. The hydrophilicity and hydrophobicity of the carbon aerogels with different amounts of ferric nitrate were measured using a contact angle meter. It was found that the higher the amount of ferric nitrate added, the larger the contact angle of the carbon aerogel and the stronger its hydrophobicity. Figure 2 ).

[0032] Both Example 1 and Example 2 confirmed that the higher the salt content, the stronger the hydrophobicity of the salt-containing carbon aerogel.

[0033] Example 3

[0034] 1.11 g of resorcinol and 0.014 g of Na₂CO₃ were dissolved in 10 ml of water and stirred until the solution was clear. Three parallel aliquots were prepared, and the same amount of cobalt nitrate was added. The mixtures were stirred for 1 hour, followed by the addition of 2 mL (0.01 mol) of formaldehyde, and stirring was continued for another hour. The solutions were then transferred to vials with varying degrees of sealing. These vials were placed in an 80°C oven for 4 days to allow for gelation and aging. The resulting gels were then frozen and dried under vacuum at -50°C in a freeze dryer for three days. The dried samples were then heated in a 1000°C N₂ atmosphere for 3 hours at a heating rate of 5°C / min to obtain cobalt-containing carbon aerogels. The hydrophilicity and hydrophobicity of the three carbon aerogels were measured using a contact angle meter. It was found that the better the sealing of the vial, the smaller the contact angle of the carbon aerogel and the stronger its hydrophilicity. Figure 3 ).

[0035] Example 4

[0036] 1.11 g of resorcinol and 0.014 g of Na₂CO₃ were dissolved in 10 ml of water and stirred until the solution was clear. Three parallel aliquots were prepared, and the same amount of nickel nitrate was added. The mixtures were stirred for 1 hour, followed by the addition of 2 mL (0.01 mol) of formaldehyde, and stirring was continued for another hour. The solutions were then transferred to vials with varying degrees of sealing. These vials were placed in an 80°C oven for 4 days to allow for gelation and aging. The resulting gels were then frozen and dried under vacuum at -50°C in a freeze dryer for three days. The dried samples were then heated in a 1000°C N₂ atmosphere for 3 hours at a heating rate of 5°C / min to obtain nickel-containing carbon aerogels. The hydrophilicity and hydrophobicity of the three carbon aerogels were measured using a contact angle meter. It was found that the better the sealing of the vial, the smaller the contact angle of the carbon aerogel and the stronger its hydrophilicity. Figure 4 ).

[0037] Examples 3 and 4 both confirmed that the better the sealing of the gelation process, the stronger the hydrophilicity of the carbon aerogel.

[0038] Example 5

[0039] 1.11 g of resorcinol and 0.014 g of Na₂CO₃ were dissolved in 10 ml of water and stirred until the solution was clear. Five parallel aliquots were prepared, and four different nitrates were added to each aliquot. The mixtures were stirred for 1 hour, followed by the addition of 2 mL (0.01 mol) of formaldehyde, and stirring was continued for another hour. The aliquots were then transferred to sealed vials and placed in an 80°C oven for 4 days for gelation and aging. The resulting gels were then frozen and dried under vacuum at -50°C in a freeze dryer for three days. The dried samples were then heated in a N₂ atmosphere at 1000°C for 3 hours at a heating rate of 5°C / min to obtain carbon aerogels containing different salts. The hydrophilicity and hydrophobicity of the carbon aerogels with different nitrates were measured using a contact angle meter, revealing that different salts had different effects on the hydrophilicity and hydrophobicity of the carbon aerogels. Figure 5 ).

[0040] Example 6

[0041] 1.11 g of resorcinol and 0.014 g of Na₂CO₃ were dissolved in 10 ml of water and stirred until the solution was clear. Three parallel aliquots were prepared and stirred for 1 hour each. Then, 0.01 mol of formaldehyde, furfural, and 2-thiophene-formaldehyde were added to each aliquot, and stirring was continued for another hour. The aliquots were transferred to sealed vials and placed in an 80°C oven for 4 days for gelation and aging. The resulting gels were then frozen and dried under vacuum at -50°C in a freeze dryer for three days. The dried samples were then heated in a 1000°C N₂ atmosphere for 3 hours at a heating rate of 5°C / min, yielding three different carbon aerogels. The hydrophilicity and hydrophobicity of these three different carbon aerogels were measured using a contact angle meter. It was found that the hydrophilicity and hydrophobicity of carbon aerogels with different precursors also differed. Figure 6 ).

[0042] Example 7

[0043] 1.11 g of resorcinol and 0.014 g of Na₂CO₃ were dissolved in 10 ml of water and stirred until the solution was clear. Three parallel portions were prepared, and stirring was continued for 1 hour. Then, 2 mL of formaldehyde was added, and stirring was continued for another hour. The solution was transferred to sealed vials and placed in an 80°C oven for 4 days to allow for gelation and aging. The resulting gels were then frozen and dried under vacuum at -50°C in a freeze dryer for three days. One sample was used as a control sample, while the other two were soaked in manganese nitrate alcohol solution and trifluoroacetic anhydride alcohol solution, respectively, for one day. After soaking, the samples were heated in a N₂ atmosphere at 1000°C for 3 hours at a heating rate of 5°C / min, yielding three types of carbon aerogels. The hydrophilicity and hydrophobicity of the three different carbon aerogels were measured using a contact angle meter. It was found that soaking in metal salt solutions or organic solvents before pyrolysis affected the hydrophilicity and hydrophobicity of the carbon aerogels. Figure 7 ).

[0044] This invention optimizes the hydrophilicity and hydrophobicity of carbon aerogel surfaces for optimal performance in various applications. For example, when using carbon aerogel as a support in electrocatalysis, the catalyst sample cannot be too hydrophilic to avoid waterlogging, nor too hydrophobic to prevent catalyst inactivation. By controlling the hydrophilicity and hydrophobicity of the carbon aerogel surface, its catalytic performance in electrocatalysis can be significantly improved. When using carbon aerogel as an oil-absorbing material, hydrophobicity is required, and hydrophobic carbon aerogels can be easily obtained through simple control methods. It is evident that this strategy for controlling the hydrophilicity and hydrophobicity of carbon aerogels has significant practical implications.

[0045] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.

[0046] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.

Claims

1. A method for controlling the hydrophilicity and hydrophobicity of carbon aerogels, characterized in that, Carbon aerogels are obtained by preparing a phenolic resin solution, followed by gelation, aging, drying, and carbonization. The hydrophilicity / hydrophobicity of the carbon aerogels can be controlled by any of the following operations: (1) A metal nitrate is added during the preparation of the phenolic resin solution, wherein the metal nitrate is manganese nitrate or ferric nitrate; by increasing the amount of metal nitrate added, the contact angle of the carbon aerogel is increased and the hydrophobicity is enhanced. (2) Adding cobalt nitrate or nickel nitrate during the preparation of phenolic resin solution changes the sealing of the gelation and aging process. By enhancing the sealing, the contact angle of carbon aerogel is reduced and the hydrophilicity is enhanced.

2. The method for regulating the hydrophilicity and hydrophobicity of carbon aerogel according to claim 1, characterized in that, A phenolic resin solution was prepared using resorcinol and aldehyde as precursors, wherein the aldehyde was selected from formaldehyde, furfural, and 2-thiophene formaldehyde.

3. The method for regulating the hydrophilicity and hydrophobicity of carbon aerogel according to claim 2, characterized in that, The specific method for preparing the phenolic resin solution is as follows: add resorcinol to an aqueous solution and stir until the solution becomes transparent. Then add sodium carbonate as a catalyst and stir for 1 hour. After stirring, add aldehyde and stir for another hour to obtain the phenolic resin solution.

4. The method for regulating the hydrophilicity and hydrophobicity of carbon aerogel according to claim 1, characterized in that, The specific method for gelation and aging is as follows: transfer the thoroughly stirred phenolic resin solution into a small bottle, seal it, and place it in an 80 ℃ oven for 4-5 days to obtain a gel.

5. The method for regulating the hydrophilicity and hydrophobicity of carbon aerogel according to claim 4, characterized in that, The specific drying method is as follows: transfer the gel to a freeze dryer, freeze dry for 3 days, and then discharge the material to obtain an organic aerogel.

6. The method for regulating the hydrophilicity and hydrophobicity of carbon aerogel according to claim 1, characterized in that, The specific method of carbonization is as follows: put the organic aerogel into a tube furnace, use nitrogen or argon as the protective gas, heat the tube furnace at a heating rate of 5℃ / min, heat to the pyrolysis temperature of 700-1000℃, hold for 3 hours, cool down, and then discharge to obtain carbon aerogel.

Citation Information

Patent Citations

  • Preparation method and application of super-hydrophobic fiber carbon aerogel

    CN109364877A

  • Preparation method of carbon aerogel

    CN106542517A

  • Superhydrophobic composite carbon aerogel oil absorbent material and preparation method thereof

    CN107020071A